Development and transition of small towns in rural China. (December 2015) - Gu, Chaolin; Li, Yan; Han, Sun Sheng
Abstract: Small towns are important drivers for China's urbanization, but at the present they have no autonomy in deciding whether or not to sell their land, what the planned future is, how urban land will be developed, whether or not to borrow and/or raise funds from the financial market. The public services and facilities such as schools, hospitals, cultural and community centers, and public housing are usually poorly developed in small towns, failing to meet the basic needs for urban growth. As such, both the development of rural China and the broader urbanization and modernization processes are checked by inadequate power of decision-making and poor services in small towns. This paper advocates the designation of a new type of city in China, i.e. "county-serviced city" (CSC, xian guan shi ), to qualified small towns within the existing administrative hierarchy. The CSC will have the same rights as all other Chinese cities in dealing with their economic development, but it will remain in its current position as a township level unit in the administrative system and continue to be served with social services and public goods by its county government. The paper is presented in seven sections with an emphasis on the principles of "decentralization" and "small government, big society", the experiences in other socioeconomic and cultural contexts, and a scenario of status-change in Nancun township, Qingdao, Shandong Province. Highlights: A new type of city – the "county-serviced city (CSC)" – was proposed in order to facilitate China's urbanization. The CSC will have all the development rights as a city but remain to be serviced by its county government. A CSC example was used to illustrate the new configuration of government offices and the provision of new facilities. CSC will nurture a sense of autonomy and further reform in China's political and economic system.